Postoperative Pain Treatment after Open Knee Surgery: Continuous Lumbar Plexus Block with Bupivacaine versus Epidural Morphine. Issue 1 (January 1991) - Schultz, P.; Christensen, E. F.; Anker-Møller, E.; Spangsberg, N.; Dahl, J. B.; Faunø, P.
Abstract : The anesthetic and side effects of a continuous lumbar plexus block ("3-in-1" block) were compared with that of epidurally administered morphine after open knee surgery. Twenty-two patients were randomized into two groups in this prospective, double-blind study. At the end of surgery, catheters were inserted for all the patients into both the femoral nerve sheath and the epidural space. Pain treatment was given as either bupivacaine in the femoral catheter or morphine in the epidural catheter, with saline in the other catheter. All treatments were given as a bolus dose followed by continuous infusion. If the patients had pain, they were given morphine intramuscularly on demand. The pain scores and supplemental morphine consumption were low in both groups and did not differ significantly. Lumbar plexus block produced a statistically significant a lower incidence of nausea, vomiting, pruritus and urinary retention. Although no significant differences in pain relief were shown between the two methods, we conclude that postoperative lumbar plexus block is preferable for postoperative pain relief because there is a lower frequency of side effects.